Ajams in Ottoman Printing: Iranian Book Company (sirket-i Sahafiye-i Osmaniye) - (:unkn) unknown (ISTANBUL 29 MAYIS UNIV & ISAM, 2020)
After the second half of the 19th century, as the printing in Ottoman Empire became widespread, the number of private printing houses increased and many new actors entered into the Ottoman printing market. Iranian entrepreneurs called Acem Basmaalar/Kitapalar ('Ajam Printers/booksellers) were important actors of this market. Some of the printers and booksellers came together to establish companies. $irket-i Sahafiye-i Iraniye (Iranian Book Company), was one of these companies and established by Iranian printers and bibliopoles operating in Istanbul to publish cheaply. It distinguished from other companies because of being a pioneer company in the Ottoman printing history and marked a quarter century in Ottoman printing. Contrary to its place in the Ottoman printing history, this company hasn't been quested independantly until now. This paper aims to discuss the establishment of the company, the identities and professions of the founders and partners of the company, the place of the print, bookstores, activities of the company, publication categories, publication policy, reader profile and the relationship of the company with the Ottoman official authorities. The paper concentrates especially on the relations of the company with censor mechanism of the Abdulhamid II Era and it will also try to answer the question that whether the Iranian identiy of the founders of the company affected the publication policy.
Keywords: Ottoman; Ajams Iranians; printing press; shirket-i sahafiye bookseller